Técnicas de espectroscopia de raios X no estudo microscópico de sistemas de elétrons fortemente correlacionados - Amaral, Robert Prudencio (2021)
In this work, we use X-ray absorption spectroscopy (XAS) techniques to investigate structural and electronic aspects of two systems with strong correlations amongst electrons. We studied the double disordered perovskite BaTi(1/2)Mn(1/2)O(3) (BTMO) and the heavy-fermion intermetallic system Ce(2)Rh(1-x) Ir(x)In(8) (x=0.00, 0.25, 0.50, 0.75, 1.00) - Ce218. BTMO was recently investigated in our research group on volumetric samples (hexagonal structure and space group R-3m, and it was characterized as magnetically frustrated throughout the measured temperature range. Studies also allowed us to suggest the BTMO as a candidate for the spin liquid. In this work, we present the quantitative results of XAS in BTMO bulk samples and epitaxial thin films. For the latter, we observed long-range magnetic order (ferro/ferri-magnetic) at 5, 100 and 300 K, apparently associated with the change in the dimensionality of the Mn-O-Mn magnetic interactions. The Ce218 system, on the other hand, was previously studied by collaborators. It was shown the appearance of two superconducting phases: the SC1 phase in the Rh-rich region, which is favored by applying pressure, and the SC2 phase, observed around the Ir concentration of x ~ 0.6, which disappears with applying pressure. With spectroscopic techniques we show that the Ir site has little structural disorder. Due to the limit of photon flux at energies of 24 keV, the XAS experiments at Rh K edge had low signal/noise ratio, making the analysis at the edge unreliable. We used EXAFS and XANES techniques together with computational simulations of multiple scatterings and atomic multiplet calculations. The BTMO thin films were epitaxially grown by Pulsed Laser Deposition (PLD) over SrTiO(3) (STO 001) substrates. We followed their chemical and physical details through X-ray diffraction, reciprocal space mapping, magnetization data, transmission electron microscopy, and atomic force microscopy.